Anatomical studies of in vitro organogenesis induced in leaf-derived explants of passionfruit - Gloria, Beatriz Appezzato da; Vieira, Maria Lucia Carneiro; Dornelas, Marcelo Carnier (Pesquisa Agropecuaria Brasileira, 1999)
With the aim of studying the organogenesis in vitro in Passiflora edulis Sims f. flavicarpa Deg., the passionfruit, leaf-derived explants were cultured on media containing NAA or BAP and incubated either in continuous darkness or in light. The histological events leading to de novo organ formation were evaluated. Darkness induces rhizogenesis in the presence of NAA, whereas direct shoot regeneration is stimulated by light and BAP. This latter condition is recommended for passionfruit micropropagation as several adventitious shoot buds were formed from meristemoids of parenchymal origin.